WILLINGNESS TO PAY KONSUMEN BERAS ORGANIK DAN FAKTOR-FAKTOR YANG BERKAITAN DENGAN KESEDIAAN KONSUMEN UNTUK MEMBAYAR LEBIH - Yulia Sari; Elly Rasmikayati; Bobby Rachmat Saefudin; Tuti Karyani; Sulistyodewi Nur Wiyono (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2020)
Increased public concern and awareness of health and environment, is expected to significantly increase organic rice consumers. Thus, it can be consumed and reached by more people. The objectives of the study were to identify the characteristics of organic rice consumers, measure willingness to pay of organic rice consumers and analyze the factors related to the willingness to pay of organic rice consumers. The method used in this study is a survey method with descriptive statistical analysis and the Contingent Valuation Method (CVM). The numbers of research respondents were 51 people consisting of organic rice consumers in Warung Sehat 1000 Kebun (W1000K) as much 18 people and consumers of organic rice in several other places joined in the Indonesian Organic Community as much 33 people. The results showed that consumers were willing to pay up to 10% higher than the price offered for organic rice types of pandan wangi, menthik susu, red rice and brown rice sold in W1000K. Even in some other places, consumers are willing to pay for those rice at prices higher up to 22% of the offered price. While for organic rice type of black rice, consumers are willing to pay 9%-11% lower than the price offered. Factors related to consumers' willingness to pay more for organic rice are health (67%), food security (45%), impact on the environment (43%), knowledge of organic rice (39%), easy access to get rice (37%), service (33%), quality (25%), packaging (24%), price (20%), and lifestyle (18%).